Inovasi Pembelajaran Musik melalui Audio Visual berbasis Multimedia Interaktif - Murcahyanto, Hary (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Education in Indonesia faces various challenges, particularly due to the Covid-19 pandemic, which has forced a shift to online learning. However, the use of technology can help overcome difficulties faced by teachers and increase interactivity and student interest in learning music arts. This study aims to evaluate the effectiveness of developing a learning media for staff notation based on Macromedia Flash 8 in enhancing student comprehension. The research methodology follows the Borg and Gall development model, involving the analysis of learning objectives, product design, implementation, expert validation, and field testing. Media content analysis focused on the learning of staff notation introduction. The research results indicate that the developed learning media successfully achieved the learning objectives. Validation by media and material experts showed positive assessments of the media’s design and content. Field testing also showed positive responses from students, indicating increased interest and understanding of staff notation material. Based on the N-Gain score calculations, the use of audiovisual media based on Macromedia Flash 8 for learning staff notation is considered quite effective, with an average N-Gain score of 0.72 and an accumulated N-Gain percentage of 72%. The conclusion of this study is that the development of audiovisual media based on Macromedia Flash 8 is effective in enhancing students' interest, understanding, and learning outcomes in staff notation material.